The girl on the train [large type] - Hawkins, Paula (Thorndike Press large print peer picks, 2015)
After witnessing something shocking, Rachel offers what she knows to the police, and becomes inextricably entwined in what happens next, as well as in the lives of everyone involved. Has she done more harm than good?